The potential of volatiles from Brassica juncea seeds against grey mould agent Botrytis cinerea and their effect on storage and sensory quality of spinach leaves - Beata Kowalska; Magdalena Szczech; Maria Grzegorzewska; Anna Wrzodak; Kalina Sikorska-Zimny (Plant Protection Science)
The potential use of volatile compounds released from milled seeds of mustard (Brassica juncea cv. Malopolska) obtained from three different companies was tested in in vitro and in vivo experiments for their inhibitory effect on Botrytis cinerea growth on agar media and its infection on vegetable leaves of cucumber, bean and spinach. In the experiments with spinach, the effect of volatiles from mustards on the storage and sensory quality of fumigated leaves was evaluated. The antifungal effect of the volatiles depended on the source and dosage of mustard seeds and biofumigation time. The most efficient inhibition of B. cinerea mycelium growth on agar media and vegetable leaves was mustard S from SHR company. The development of grey mould on spinach leaves was inhibited in the treatment with 4 h biofumigation with the volatiles from mustard S seeds in experiments conducted at 10 °C and also at 18 °C. In the sensory and storage quality analysis, the spinach leaves treated with volatiles from mustard seeds showed acceptable parameters that predisposed the product to consumption. The results show that it is possible to reduce the incidence of vegetable grey mould with the treatment of milled mustard seeds, opening a potential application of biofumigation in the control of B. cinerea in vegetables.